2016
DOI: 10.1038/icb.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

A central role for hepatic conventional dendritic cells in supporting Th2 responses during helminth infection

Abstract: Dendritic cells (DCs) are the key initiators of T helper (Th) 2 immune responses against the parasitic helminth Schistosoma mansoni. Although the liver is one of the main sites of Ag deposition during infection with this parasite, it is not yet clear how distinct DC subtypes in this tissue respond to S. mansoni Ags in vivo, or how the liver microenvironment might influence DC function during establishment of the Th2 response. In this study, we show that hepatic DC subsets undergo distinct activation processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
(150 reference statements)
3
23
0
Order By: Relevance
“…Notably, in most cases, the degree to which activation molecules were upregulated was less striking with SEA than St ( Fig EV1). This muted cDC surface activation following exposure to SEA is in keeping with previous reports of GMDCs or human PBMC DCs exposed to SEA in vitro, or splenic and hepatic DCs from S. mansoni-infected mice, and may reflect an alternative, and more restricted, DC activation phenotype that is common to Th2 settings (MacDonald et al, 2001;de Jong et al, 2002;Straw et al, 2003;MacDonald & Maizels, 2008;Lundie et al, 2016).…”
Section: An Ifn-i Signature and Th2 Induction By Fldcssupporting
confidence: 90%
“…Notably, in most cases, the degree to which activation molecules were upregulated was less striking with SEA than St ( Fig EV1). This muted cDC surface activation following exposure to SEA is in keeping with previous reports of GMDCs or human PBMC DCs exposed to SEA in vitro, or splenic and hepatic DCs from S. mansoni-infected mice, and may reflect an alternative, and more restricted, DC activation phenotype that is common to Th2 settings (MacDonald et al, 2001;de Jong et al, 2002;Straw et al, 2003;MacDonald & Maizels, 2008;Lundie et al, 2016).…”
Section: An Ifn-i Signature and Th2 Induction By Fldcssupporting
confidence: 90%
“…Interestingly, some studies suggest that ILC, 129-131 basophils, [132][133][134] and eosinophils 135,136 can express major histocompatibility complex class II and directly prime Th2 responses, notably upon N. brasiliensis 131 and T. muris 132 infections, with each cell type having been shown to migrate to the mesenteric lymph nodes during infection. 85,87,137,138 However, given that protective immunity is abolished in mice where all 139,140 or specific subsets 104-106,108,109 of dendritic cells have been depleted, it is perhaps more likely that these other innate cells contribute to local tissue immunity by promoting dendritic cell activation, or by further enhancing the cytokine response of mature T cells that have migrated to the infected tissue. 53 Moreover, dendritic cells are responsive not only to cytokines produced by other innate cells, but also to epithelium-derived cytokines, including TSLP, 54,[141][142][143] IL-25, 144 and IL-33, 52,145 thus potentially bypassing ILC2 and granulocytes entirely.…”
Section: Inductionmentioning
confidence: 99%
“…Ma et al uncovered a novel subset of CD11c + CD49b + FcεRI + DCs that can produce IL-4 and subsequently promote Th2 differentiation in an IL-4-dependent manner (146). However, contradictory findings revealed that conventional DCs are critical subsets for Th2 effector cell development during acute S. mansoni infection (147). In fact, more researchers support the notion that DCs do not need to produce IL-4 to promote Th2 development (148)(149)(150) because IL-4-deficient DCs still show the ability to induce excellent Th2 responses (148).…”
Section: The Impact Of Other Immune Cells On Cd4 + T Cells and Regulamentioning
confidence: 99%